KERAGAMAN JENIS RAYAP PADA BERBAGAI TIPE PENGGUNAHAN LAHAN DI DESA RAHMAT KECAMATAN PALOLO KABUPATEN SIGI - Saldi, Saldi; Wardah, Wardah; Yusran, Yusran (Warta Rimba, 2015)
Termites play important roles in organic matter decomposition, nutrient cycling, and soil structure in tropical rain forests. When forests are replaced by agriculture, termite species richness, abundance, and function often decline. This research was aimed to determine diversity and composition of termites in three land use types (community forest, simple and complex agroforestry). The method used in this study is collecting termites sampled on transects measuring 2 x 100 m, divided into 20 sections (2 x 5 m). The collected samples were collected for identification purposes. Variables measured the diversity of termites which includes the type and number of species (species richness) found in each land use. Diversity and abundance of species of termites were analyzed using the Shannon Diversity Index-Wienner (Shannon & Weaver, 1994 in Magurran, 2004). The results showed that the total number of termite species founded in both area was 6 species comprising 2 families, i.e; termitidae and rhinotermitidae. Alpha diversity of termite founded in community forest was 4 species, and 5 species founded in complex agroforestry and 3 species founded in simple agroforestry. The highest frequency of termite species was 0,5 that achieved by Odontotermes sp in community forest and simple agroforestry, while the lowest frequency was 0,05 that achieved by Schedorhinotermes sp. in community forest. Further, the Shannon species diversity Index (Hâ) of each land use types were 0,93, 0,95 and 1,47 in simple agroforestry, community forest and complex agroforestry, respectively. Keywords: Diversity, Termites, Land use types.